Cryobiology and Cryomedicine Techniques’ Boosting in Wartime - Goltsev, Anatoliy; Bondarovych, Mykola; Volkova, Nataliia; Lutsenko, Olena; Gaevska, Yuliia; Babenko, Natalia; Chelombytko, Olha; Ostankov, Maksym; Vvedenskyi, Dmytro; Kisielova, Hanna; Dubrava, Tetiana (Problems of Cryobiology and Cryomedicine, 2023)
The review surveys the published data on a strong negative impact of psycho-emotional stress, which accompanies both the military servicemen and civilians of any state in martial law period. Such a load can lead to severe disorders of the systems that ensure the human body homeostatic stability, in particular to post-traumatic stress disorder. In this case human body is subjected to a state accompanied by the development of severe oncology and autoimmune diseases, as well as dysfunction of the male reproductive system. The study offers modern approaches to the treatment of the listed pathologies, most of which are based on the international experience of clinical and experimental research as well as achievements of national academic science. Special attention is paid to the development of cryobiological and cryomedical cell-tissue techniques, the use of those can be promising in the strengthening of both mental and physical health of civilian population during the wartime. Probl Cryobiol Cryomed 2023; 33(2):077-102